(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article discusses the problems of intercultural communication. Intercultural experience and intercultural competence represent one of the most important ways to communicate with other cultures. Intercultural communication is the main purpose of training in the study of a foreign language. Learn a foreign language is primarily to confirm one’s identity. People try to respect cultures, beliefs, life styles of other people, they go up to full understanding without losing their own identity. To live in a cross-cultural communication experience means to leave in order to go back, to be in contact with other cultures and to reshape oneself in the function of proximity and remoteness. Language is not only a means of communication, it is a symbolic order where ideas, perceptions, values, finds its origin. One of the main purposes of communication between people of different cultures is the acquisition of intercultural competence, to do this we need to know the cultural codes of other people.